2018
DOI: 10.1038/s41598-018-22761-4
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded neural networks improving fish species prediction accuracy: the role of the biotic information

Abstract: Species distribution is the result of complex interactions that involve environmental parameters as well as biotic factors. However, methodological approaches that consider the use of biotic variables during the prediction process are still largely lacking. Here, a cascaded Artificial Neural Networks (ANN) approach is proposed in order to increase the accuracy of fish species occurrence estimates and a case study for Leucos aula in NE Italy is presented as a demonstration case. Potentially useful biotic inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…The present research has shown fish distributional changes in a context of climate warming; these results, based on observational data, can be useful for planning future management scenarios [78], also in light of the fact that the climate models predict further strong impacts on freshwater fish [64]. In particular, the possible conservation strategies that can be suggested for fish biodiversity conservation under climate-induced impacts are: (i) the maintenance of ecological flow, whereas the natural variability of the flow rate is indispensable for the conservation of habitat suitable for the life of freshwater fishes [3]; (ii) the restoration of river connectivity in order to provide opportunity, to fish species with low thermal tolerance, to move towards thermal optimum considering, however, the possibility of maintaining barriers in the event of a need to prevent the rise of exotic species; (iii) the establishment of protection areas where total autochthonous assemblages are preserved and thus play a key role in maintaining biodiversity; (iv) improvement of water quality in polluted rivers is needed to reduce additional anthropogenic stressors for resilient fish populations to adapt to climate change; (v) the restoration of riparian areas to provide shade and have directly cooling effect on river temperature [79].…”
Section: Discussionmentioning
confidence: 58%
“…The present research has shown fish distributional changes in a context of climate warming; these results, based on observational data, can be useful for planning future management scenarios [78], also in light of the fact that the climate models predict further strong impacts on freshwater fish [64]. In particular, the possible conservation strategies that can be suggested for fish biodiversity conservation under climate-induced impacts are: (i) the maintenance of ecological flow, whereas the natural variability of the flow rate is indispensable for the conservation of habitat suitable for the life of freshwater fishes [3]; (ii) the restoration of river connectivity in order to provide opportunity, to fish species with low thermal tolerance, to move towards thermal optimum considering, however, the possibility of maintaining barriers in the event of a need to prevent the rise of exotic species; (iii) the establishment of protection areas where total autochthonous assemblages are preserved and thus play a key role in maintaining biodiversity; (iv) improvement of water quality in polluted rivers is needed to reduce additional anthropogenic stressors for resilient fish populations to adapt to climate change; (v) the restoration of riparian areas to provide shade and have directly cooling effect on river temperature [79].…”
Section: Discussionmentioning
confidence: 58%
“…In this respect, the ecological variables that can be taken into account are often characterized by complex and non-linear dependencies [7]. Ecological models have been increasingly applied in the management and conservation of freshwater fish communities, especially to predict spatial patterns of fish occurrence [8], [9]. In particular, Artificial Neural Networks (ANNs) modeling has proved to be a valuable method in order to assess whether predictable relationship between environmental descriptors and fish species richness exist in small stream environments [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, each MPN2 has a single output neuron. CMPN has been applied in other ecological studies when a correlation exists among output variables (Franceschini et al, 2018).…”
Section: Rationale Of the Model And Structure Of The Cascaded Multilamentioning
confidence: 99%
“…This structural characteristic of MPN can be used to evaluate the relative influence of the input variables: if the values of a single input variable are changed (while those for the other input variables are kept the same) it is possible to observe the related effects on the outputs. Therefore, if this procedure is applied, for each input variable, by perturbing the input values at defined levels, the comparisons of the effects on the output values can be used to assess the relative influence (importance) of the input variables (Scardi and Harding, 1999;Franceschini et al, 2018). Hence, to evaluate the contributions of the independent variables to the prediction accuracies, a set of perturbation levels [initial values 5 ±0.1, ±0.2, ±0.3, ±0.4, and ±0.5] was applied, and the related effects on the output values were measured as the mean square errors (MSE) of the CMPN outputs with respect to the values in the test datasets.…”
Section: Model Validation and Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation